Selection of warehouse location for a global supply chain: A case study. Issue 4 (December 2018) - Singh, Rajesh Kr; Chaudhary, Nikhil; Saxena, Nikhil
Abstract: This study is based on an India case, where an auto components manufacturing organisation is planning to expand its business in Iran. Recently, the Government of Iran has announced incentives for industrial activities in Special Economic Zones (SEZs) and Free Trade Zones (FTZs). The purpose of this study is to illustrate the selection of most optimal location for a warehouse in various SEZs and FTZs in Iran on the basis of different criteria for warehouse location selection. Fuzzy AHP methodology has been used to choose the best out of four options available for effectiveness of supply chain.